Permeability measurements on mitochondria from wild-type and poky strains of Neurospora crassa. - Katkocin, D M (1976)
The permeability properties of isolated Neurospora mitochondria were determined by measuring the rate at which the mitochondria swell in isotonic solutions of various organic and inorganic molecules. Like mammalian mitochondria, wild-type Neurospora mitochondria were impermeable to sucrose and only slightly more permeable to most inorganic ions (K, Na, Cl). Their permeability to K was greatly increased by valinomycin and by monensin. In addition, the mitochondria contain specific systems mediating PO4 uptake and PO4- malate, fumarate, and succinate exchange. Mitochondria from the maternally inherited poky strain of Neurospora, previously demonstrated to possess defective ribosomes and a grossly cytochrome chain, showed a slight but significant increase in permeability to inorganic ions. They contained, however, the specific uptake and exchange systems for phosphate and dicarboxylate anions, a result suggesting that these systems do not depend upon mitochondrially synthesized polypeptides.